'I remember little. Almost nothing'. Participatory theatre as a means to access subjugated memories. (April 2022) - Niziołek, Katarzyna
The article presents and discusses the interdisciplinary, collaborative and participatory research project Bieżenki . Thematically, the project is devoted to the history of the so-called bieżeństwo – a migration of people from eastern Poland during the First World War, forced by the retreating Russian Army, when the Germans broke through the eastern frontline in 1915. The stories of those refugees, among whom were a number of Rus' peasants, and within that group, women with children (the term bieżenki signifies female war refugees), make up a crucial part of the regional history that has been largely absent from public knowledge and historical discourse. Methodologically, the project is based on participatory theatre that engages non-artists both as content providers, and on-stage performers. Theatrical practice has been used to collect the marginalised memories of bieżeństwo (as they are often kept and transmitted within family circles), and present them to the wider public in the form of theatrical performance. The project has also resulted in a theoretical concept of the assemblage of memory, inspired by and grounded in the creative process, which is briefly sketched out at the end of the article.